2019
DOI: 10.1055/s-0039-1688484
|View full text |Cite
|
Sign up to set email alerts
|

A Decision-Analytic Approach to Addressing the Evidence About Football and Chronic Traumatic Encephalopathy

Abstract: Doubts can be raised about almost any assertion that a particular exposure can lead to an increase in a given adverse health effect. Even some of the most well-accepted causal associations in public health, such as that linking cigarette smoking to increased lung cancer risk, have intriguing research questions remaining to be answered. The inquiry whether an exposure causes a disease is never wholly a yes/no question but ought to follow from an appraisal of the weight of evidence supporting the positive conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…If we do something, and we learn later that the hazard was not really a hazard, there may be harm done. If we do nothing, and the hazard was in fact a hazard, there will be harm done of a very different sort (163).…”
Section: Discussionmentioning
confidence: 99%
“…If we do something, and we learn later that the hazard was not really a hazard, there may be harm done. If we do nothing, and the hazard was in fact a hazard, there will be harm done of a very different sort (163).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the statement that "A cause-and-effect relationship has not yet been established between CTE and sports-related concussions or exposure to contact sports" is incomplete: a more honest summary might have read "The strong statistical associations found between CTE and SRCs or exposure to contact sports may not represent a true cause-and-effect relationship, but at present attempts to attribute these associations to confounding, bias, or artifacts have not been persuasive". 20 We also note that prospective longitudinal studies of a well-characterized cohort, the claimed sine qua non of the establishment of a causal link between repetitive head trauma and later-in-life neurodegenerative diseases, are not only impractical but also unethical in light of the significant probability of patient harm. As many as seven decades might separate a particular individual's exposure and the emergence of neurological signs and symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, there have been many published narrative and systematic reviews relating to possible long-term effects of SRC and participation in contact, collision and combat sports. 1-13 29 31 34 37-41 47 49 50 53 55 100 101 The topics of those reviews included neurological diseases, CTE, psychiatric disorders, suicide, neuroimaging and neuropsychological outcomes. The authors of past reviews have often concluded that the general quality of the evidence was low, and that high-quality cohort studies were needed.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%